Transfusion of Cryopreserved Packed Red Blood Cells Is Safe and Effective After Trauma. Issue 3 (September 2015) - Schreiber, Martin A.; McCully, Belinda H.; Holcomb, John B.; Robinson, Bryce R.; Minei, Joseph P.; Stewart, Ronald; Kiraly, Laszlo; Gordon, Nicole T.; Martin, David T.; Rick, Elizabeth A.; Dean, Rondi K.; Wiles, Connor; et al.
<x xml:space="preserve">Abstract</x> Objectives: To determine the safety and efficacy of cryopreserved packed red blood cell (CPRBC) transfusion in trauma patients. Background: Liquid packed red blood cells (LPRBCs) have an abbreviated shelf-life and worsening storage lesion with age. CPRBCs are frozen 2 to 6 days after donation, stored up to 10 years, and are available for 14 days after thawing and washing. CPRBCs can be utilized in diverse settings, but the effect on clinical outcomes is unknown. Methods: We performed a prospective, randomized, double-blind study at 5 level 1 trauma centers. Stable trauma patients requiring transfusion were randomized to young LPRBCs (⩽14 storage days), old LPRBCs (>14 storage days), or CPRBCs. Tissue oxygenation (StO2), biochemical and inflammatory mediators were measured, and clinical outcomes were determined. Results: Two hundred fifty-six patients with well-matched injury severity and demographics (P > 0.2) were randomized (84 young, 86 old, and 86 CPRBCs). Pretransfusion and final hematocrits were similar (P > 0.68). Patients in all groups received the same number of units postrandomization (2 [1–4]; P > 0.05). There was no difference in the change in tissue oxygenation between groups. CPRBCs contained less α2-macrogobulin, haptoglobin, C-reactive protein, and serum amyloid P (P < 0.001). Organ failure, infection rate, and mortality did not differ between groups (P > 0.2). Conclusions: Transfusion of CPRBCs is as safe and effective as transfusion of young and old LPRBCs and provides a mechanism to deliver PRBCs in a wide variety of settings.